Analogi Gramatikal Berbasis Ayat Al-Qur'an dalam Pembelajaran Nahwu Dasar pada Santri Tahfiz - Saputra, Ahmad Rifan Arya; Finurika, Isna (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study examines the implementation of grammatical analogies based on Quranic verses in basic Arabic syntax instruction for Tahfidz (Quran memorization) students at the Sunan Drajat Islamic Boarding School in Lamongan. The research aims to identify the forms of grammatical analogies derived from Quranic verses, describe their implementation in the learning process, and analyze their contribution to the students' understanding of syntax. A qualitative approach with a case study design was employed. Primary data were obtained from syntax teachers, supervisors, and students, while secondary data were gathered from relevant literature. Data collection involved observation, in-depth interviews, and documentation. Data analysis utilized the interactive model proposed by Miles, Huberman, and Saldaña—comprising data condensation, data display, and conclusion drawing—while data validity was ensured through source triangulation, technique triangulation, and member checking. The results reveal nine dominant forms of grammatical analogies used in basic syntax instruction: mubtada’–khabar, fi‘il–fa‘il, maf‘ul bih, jar wa majrur, mudhaf–mudhaf ilaih, na‘at–man‘ut, isim isyarah, inna wa akhawatuha, serta kana wa akhawatuha. The implementation of these analogies proceeded through three stages—planning, instruction, and evaluation—utilizing Quranic verses already familiar to the students as the primary learning resources. Furthermore, the study demonstrates that Quran-based grammatical analogies positively contribute to students' understanding of syntactic rules, syntactic analysis skills, Arabic text reading proficiency, and motivation to learn. Therefore, integrating tahfidz activities with syntax instruction—using grammatical analogies derived from Quranic verses—serves as a contextual and meaningful learning strategy to strengthen both the grammatical competence and Quranic understanding of tahfidz students.